FORMULASI DAN UJI AKTIVITAS TABIR SURYA DAN ANTIOKSIDAN KRIM O/W NANOKITOSAN - , ELSA MARISA PARDEDE ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The ability of chitosan to form edible films can be applied as sunscreen and antioxidants. Chitosan in the form of nanoparticles will increase the effectiveness as a sunscreen and antioxidants. The aims of this research is to obtain the optimum formula nanochitosan o/w cream and knowing the physical properties and stability, also its activity as sunscreen and antioxidants. Nanochitosan formulated in o/w cream with the composition of stearic acid, cetyl alcohol and TEA as an emulsifier which is optimized using Simplex Lattice Design. All formulas are tested its physical properties, including viscosity, dispersive power, and adhesion power to obtain optimum formula. Optimum formula cream with varying nanochitosan composition is 0,1% (A)